2019
DOI: 10.1101/698928
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Cell Fate Clusters in ICM Organoids Arise from Cell Fate Heredity & Division – a Modelling Approach

Abstract: During the mammalian preimplantation phase, cells undergo two subsequent cell fate decisions. During the first cell fate decision, cells become either part of an outer trophectoderm or part of the inner cell mass. Subsequently, the inner cell mass segregates into an embryonic or an extraembryonic lineage giving rise to the epiblast and the primitive endoderm, respectively. Inner cell mass organoids represent an experimental model system for preimplantation development, mimicking the second cell fate decision t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 55 publications
0
2
0
Order By: Relevance
“…The functional relevance of the clustering effect might be to ensure an early coordinated PrE cell behaviour during their migration in later stages to occupy their final position at the blastocoele. Recent modelling results for cell population development in ICM organoids show that clonal expansion can play a role in clustering [58]. In addition, the substantial cellular rearrangements taking place during preimplantation development [28,59] might have a positive effect on cell fate clustering.…”
Section: Early Blastocysts Exhibit Patterns In Local Positional Featumentioning
confidence: 99%
“…The functional relevance of the clustering effect might be to ensure an early coordinated PrE cell behaviour during their migration in later stages to occupy their final position at the blastocoele. Recent modelling results for cell population development in ICM organoids show that clonal expansion can play a role in clustering [58]. In addition, the substantial cellular rearrangements taking place during preimplantation development [28,59] might have a positive effect on cell fate clustering.…”
Section: Early Blastocysts Exhibit Patterns In Local Positional Featumentioning
confidence: 99%
“…Indeed, the two populations of cells are generated in precise proportions and with a reproducible timing, but their spatial patterning is random as it exhibits a salt-andpepper pattern (Chazaud et al, 2006). Models of the associated GRN revealed that ICM differentiation corresponds to a self-organized system relying on bi-or tri-stability (Bessonnard et al, 2014;Liebisch et al, 2020;Saiz et al, 2020;Raina et al, 2021;. These models are all based on the cross-inhibition between the NANOG and GATA6 transcription factors that characterize the Epi and PrE states, respectively.…”
Section: Introductionmentioning
confidence: 99%